Trends in digitization of the supply chain: A brief literature review - Jose Marmolejo-Saucedo; Scarlett Hartmann (EAI Endorsed Transactions on Energy Web, 2020)
The latest advances in technology, reﬂected as the Industrial Revolution 4.0, have forced the digitization of supply chains and logistics in general. Only companies that can prepare for and embrace change will survive in the new business environment. Businesses in industries that do not adapt to the new rules of the game will become obsolete in market share. The transformation of a supply and logistics chain, from an old model to a digital one, requires strict organization. It is a great eﬀort on a human level, with the ease of requiring low operating costs. The reward for achieving this change is openness to a global business, where the possibilities grow exponentially and proportionally with the capacity of the available work team. Big data emerges as the beginning of the digitization of supply chains and logistics in the global world. The new environment requires a permanent update of the services software based on market needs. Generally, this does not imply changing technology immediately. However, the goal is to be ready for evolution when a novelty means improvement. This paper brieﬂy presents the evolution of supply chains in the digital context of operational functions.